Evaluation of Laser in Situ Keratomileusis Outcomes in Cipto Mangunkusumo Hospital - Habsyiyah Habsyiyah; Amir Shidik; Tri Rahayu (Majalah Oftalmologi Indonesia, 2015)
Background: The aim of this study is to evaluate the efficacy, predictability and safety of the first experience in laser in situ keratomileusis (LASIK) surgery using Wavelight Refractive Suite in Kirana Cipto Mangunkusumo HospitalMethods: Design of this study was descriptive retrospective. Data of patients who underwent LASIK surgery from April 2012 to January 2013 were collected. The data consist of pre and post operative refractions, uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA).Results: Fifty eight eyes of 31 patients, 13 males and 18 females, mean age of 28 year-old were analyzed. The mean spherical error corrected was -6,42 ± 3,37 D with range of -1.25 D to -16,87D. Median UCVA post surgery 1 day, 1 week, and last follow up time were 6/7,5, 6/6, and 6/6 respectively. Postoperatively, 91,67% eyes achieved UCVA of 6/12 or better with 77,78% achieving 6/7,5 or better. One patient lost 1 Snellen line of BCVA became 6/6,6. The mean postoperative manifest refraction spherical equivalent was -0,24 (±0,42) D. The general refractive predictability was 88,2% within ±0.5D from the target refraction, while 94,1% within ±1D ofthetarget.Conclusion: LASIK surgery performed in Kirana Cipto Mangunkusumo Hospital is safe and effective with good refractive predictability.